Early Muslim Historiogrphy : a study of Early Transmitters of Arab History from the Rise of Islam up to the end of Umayyad Period. (612 - 750 A.D.) - Nisar Ahmed Faruqi (Idarah-I Adabiyat-I, 1979)
tr, c.1